AI-Powered Retail Analytics: Leveraging Spatial Data for Enhanced Store Performance - Vinodhini Chandrasekaran (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive technical article examines the transformation of retail operations through AI-driven spatial analytics and advanced tracking technologies. It explores the integration of customer behavior data with spatial analytics, providing retailers with unprecedented insights into shopping patterns and customer journeys. The article investigates various aspects of retail analytics implementation, including data collection infrastructure, journey analysis frameworks, and transaction integration systems. It demonstrates how retailers can leverage these technologies to optimize store layouts, enhance marketing strategies, and improve overall operational efficiency. The article also addresses critical technical considerations such as privacy, security, and system scalability, while exploring future developments in retail analytics. Through detailed examination of multiple data sources and advanced analytical techniques, this article provides valuable insights into the practical applications and benefits of AI-powered retail analytics, offering retailers a roadmap for implementing data-driven decision-making processes to enhance customer experience and business performance.
Keywords: Retail Analytics; Spatial Data Analysis; Customer Journey Tracking; AI-Powered Retail; Privacy-Preserving Analytics